Bare bones a survey of forensic anthropology - Warren, Michael W.; Parr, Nicolette M.; Zambrano, Carlos J.; Skorpinski, Katherine E. (Dubuque Kendall Hunt, 2011)
Update of 2008 edition with minor corrections and more photographic examples.
Medicolegal aspects of death -- What is forensic anthropology? -- Recovery, documentation, and preparation of human remains -- Taphonomy -- Human osteology and osteometry -- Determination of biological sex -- Determination of ancestry -- Determination of age at death -- Determination of stature -- Personal identification -- Forensic art -- Interpreting skeletal trauma -- Burned and cremated bodies -- Mass fatalities -- Human rights missions -- The profession of forensic anthropology.
Includes bibliographical references and index.
ASP-1361g donated by
Keywords: Forensic anthropology